Issues of Realization of the Right to Fair and Public Hearing in Reasonable Time in Civil Procedure in the Light of Constitutional Reforms - Hovhannisyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The right to fair and public hearing (case examination) in reasonable time that is being deemed as an element to the right to fair trail and criteria of evaluation of reasonableness have been recently intoduced to the legal system of the Republic of Armenia (the RA). The lack of scientific analyses in domestic jurisprudence and judicial precedent for the subject matter should be noted, which may cause problems for reserving the procedural norms guarantying this right, correct interpretation and implementation of provisions stipulated by the RA Constitution and international treaties. As a result of scientific analysis of approaches which are formed in ECHR’s precedent law regarding the right to case examination in reasonable time, the author has elaborated suggestions directed towards revealing the very essence of this right in civil procedure, has established legal framework for its realization and preservation, as well as its evaluation standards. Moreover, establishment of civil-procedural frame for the action of the right not only will entail the maximum discovery of the substance of reasonableness of the case examination term, but also will make is easy to evaluate the violations of this right adequately. The author has concluded, that the rights to litigation and execution of judicial act in reasonable time assume such duration and timeframe provided by the state (via the court or the Compulsory Enforcement Service), during which the initial meaning of the applicant’s subjective right (that is subject to protection) will be guaranteed in maximum. Moreover, it has been specially emphasized, that the timeframes established by the law shall also be reasonable and the evaluation of whether the case has been examined in reasonable time may be carried out with collation and unity of standards established exclusively by the Code.
Keywords: Reasonable time, case examination, litigation, evaluation standard, right to a fair trial, violation of right, compensation claim